Celebrate : joyful baking all year round - Hollywood, Paul (Bloomsbury Publishing, 2025)
"Paul Hollywood, the best baker in the business, is back with Celebrate: showstopping bakes to mark the special moments in your life. Having been a judge on Bake Off for over a decade and a professional baker for even longer, Paul knows the joy of baking and how it can be one of celebratory fun. With chapters on Spring, Summer, Autumn and Winter as well as Party Food and Cakes, you will have something up your sleeve for every occasion, from Easter and Christmas, to summer picnics, Valentine's Day and much more. Including recipes for easy traybakes, layer cakes, quiches, tarts, breads, pastries, desserts and cookies, expect family favourites like Mini Chocolate Logs and twists on classics like Strawberry Heart Scones, as well as Paul's delectable Bake Off Cake and scrumptious handheld beef pies. Filled with his fool-proof recipes and kaleidoscopic photography, Celebrate makes the occasions that mean the most to us all the more memorable"--Publisher's description.